2003
DOI: 10.1063/1.1628225
|View full text |Cite
|
Sign up to set email alerts
|

Competing interactions of noble metals and fullerenes with the Si(111)7×7 surface

Abstract: Synchrotron-based photoelectron spectroscopy (PES) has been used to investigate the interaction of atomic gold and silver with a covalently bound C60-monolayer adsorbed on Si(111)7×7. In contrast to the relatively benign interaction of silver with the C60/Si(111)7×7 surface, core-level photoemission data reveal a strong interaction of gold with the underlying silicon despite the presence of a chemisorbed fullerene monolayer. The Si 2p PES data exhibit dramatic changes consistent with the formation of a gold si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…1,5,35 In the case of Au, XPS, AFM, and IR, results indicate that OTS monolayers are similar to oxide surfaces while directly attached monolayers are similar to H-terminated silicon surfaces highlighting the importance of the substrate in the reactivity under the metal. Previous work has shown that Au reacts with silicon to form a Au 3 Si silicide, 33,34 and the XPS Au core level results are consistent with gold silicide formation. This likely alters the surface chemistry enough to displace the monolayers.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…1,5,35 In the case of Au, XPS, AFM, and IR, results indicate that OTS monolayers are similar to oxide surfaces while directly attached monolayers are similar to H-terminated silicon surfaces highlighting the importance of the substrate in the reactivity under the metal. Previous work has shown that Au reacts with silicon to form a Au 3 Si silicide, 33,34 and the XPS Au core level results are consistent with gold silicide formation. This likely alters the surface chemistry enough to displace the monolayers.…”
Section: Resultssupporting
confidence: 70%
“…The observation of only one Ag oxidation state indicates that Ag does not react with the underlying silicon substrate as expected from previous results showing that silicon and silver do not form a silicide. 34,36 Figure 13 shows the atomic fractions for Ag, Si, C, and O as a function of sputtering time for the alcohol and OTS surfaces. The area of the C 1s peak for the interfacial region (30-75 s) is nearly equivalent for both the alcohol and the OTS in agreement with the observation of organic monolayers under Ag in the IR (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…This large shift from the position of metallic Au ( ) indicates a strong interaction between the Au overlay and the Si substrate. This shift is in agreement with earlier studies on annealed Au silicide structures on Si(111) substrates 17 , 52 , 53 and is considerably larger than reported for Au silicide layers obtained at room temperature 16 , 47 , 54 . The branching ratio reduces from about 0.72 for photons to about 0.58 for , while the spin-orbit splitting is taking into account all measurements.…”
Section: Resultssupporting
confidence: 93%
“…Thus, the -component is assigned to the Si bulk. Based on the previous reports on Au silicide structures 16 , 17 , 47 , 52 54 , the highest binding energy component can be assigned to Si in Au silicide although the here found chemical shift of this component is slightly lower than the previously reported values. The -component is related to Si at or near the surface, but not bound to Au atoms.…”
Section: Resultssupporting
confidence: 52%
“…Following a well-established approach [31] , [32] , a C 60 monolayer (ML) was formed on the Si(111)-(7×7) surface to act as a template for the formation of Ag nanoparticles. (This strategy cannot be used to form Au nanoparticles [33] , such as those studied by Stellacci et al As feedback ringing and imaging artefacts are entirely independent of the composition of the nanoparticle, however, our results are equally applicable to Au nanoparticles.) C 60 was first sublimed onto a clean Si(111)-(7×7) surface, formed using standard flash annealing procedures [34] .…”
Section: Methodsmentioning
confidence: 56%